Messages from Manchester: pilot randomised controlled trial following self-harm. - Kapur, N; Gunnell, D; Hawton, K; Nadeem, S; Khalil, S; Longson, D; Jordan, R; Donaldson, I; Emsley, R; Cooper, J (2013)
Studies of therapeutic contact following self-harm have had mixed results. We carried out a pilot randomised controlled trial comparing an intervention (information leaflet listing sources of help, two telephone calls soon after presentation and a series of letters over 12 months) to usual treatment alone in 66 adults presenting with self-harm to two hospitals. We found that our methodology was feasible, recruitment was challenging and repeat self-harm was more common in those who received the intervention (12-month repetition rate 34.4% v. 12.5%).